Tin bronze alloy welding wire and preparation method thereof

By controlling the content of elements such as Sn, P, Zn and other elements in tin bronze alloy welding wire and adding elements such as Ni, Ti, Pb, Si and La, their microstructure structure is optimized, and the problems of thermal cracks and pores during welding are solved, and the bonding strength and tissue stability after welding are improved.

CN119549925APending Publication Date: 2025-03-04NINGBO POWERWAY ALLOY MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411815051.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing tin bronze alloy welding wires are prone to thermal cracks and pores during welding, resulting in poor welding performance and insufficient bonding strength after welding.

Method used

By controlling the content and microstructure structure of elements such as Sn, P, Zn, etc., a specific tin bronze alloy welding wire is prepared, with a mass percentage composition of: Sn: 7-13 wt%, P: 0.02-0.15 wt%, Zn: 0.005-0.1 wt%, and other elements such as Ni, Ti, Pb, Si and La were added to the welding wire to optimize the microstructure of the alloy.

Benefits of technology

The presence of pores after welding is significantly improved, the bond strength and structure stability after welding is improved, and the copper-based cladding layer after welding has high-quality denseness and excellent performance working layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549925A_ABST
    Figure CN119549925A_ABST
Patent Text Reader

Abstract

The invention discloses a tin bronze alloy welding wire and a preparation method thereof, the tin bronze alloy welding wire comprises the following components in percentage by mass: 7-13 wt% of Sn, 0.02-0.15 wt% of P, 0.005-0.1 wt% of Zn and other elements with the total amount of less than 3.5 wt%, the other elements are selected from one or more of Ni, Ti, Pb, Si and La, the Ni is less than or equal to 3.0 wt%, the Ti is less than or equal to 0.75 wt%, the Pb is less than or equal to 0.15 wt%, the Si is less than or equal to 0.1 wt%, the La is less than or equal to 0.1 wt%, and the balance is Cu and inevitable impurities; the preparation method comprises the working procedures of smelting, casting, homogenizing annealing, cold machining and peeling, stress relief annealing and reducing drawing. According to the welding wire, growth of crystal grains during welding can be effectively inhibited, a post-welding structure with uniform components is obtained, and the air hole existence condition in a post-welding copper-based cladding layer is obviously improved, so that a post-welding working layer with excellent forming effect and performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy materials, and in particular relates to a tin bronze alloy welding wire and a preparation method thereof. Background Art

[0002] With the increase in the demand for high power in the wind power field, rolling bearings are getting bigger and bigger, and cannot support the next iteration of high-power wind turbines. For this reason, a new welding process has emerged. Sliding bearings can be prepared by welding to replace traditional rolling bearings. When used in wind turbines, it can effectively reduce the weight of wind turbines and increase their service life. The sliding bearing obtained by welding is a copper-steel bimetallic composite material, which is composed of a copper alloy and a steel matrix. The steel matrix plays a role in bearing and impact resistance, while the copper alloy layer is the working layer of the friction pair components, which is required to have a low friction coefficient, good fatigue resistance and corrosion resistance.

[0003] Tin bronze can be used as one of the preferred materials for copper-steel bimetallic composite materials due to its good corrosion and wear resistance, good mechanical properties, and high strength after welding. However, due to its low high-temperature strength and plasticity, tin bronze has great hot brittleness and is prone to thermal cracking during welding. In addition, tin bronze has a wide liquid-solid temperature range and severe segregation, which can easily generate coarse and fragile dendritic structures, making the welding cladding layer or weld loose, and even forming pores, resulting in poor performance of the cladding layer or weld formed by welding. Therefore, it is an urgent problem to provide a tin-bronze alloy welding wire that can improve the existence of pores after welding while ensuring excellent bonding strength after welding, and provide high-quality and stable post-weld structure. Summary of the invention

[0004] The first technical problem to be solved by the present invention is to provide a tin-bronze alloy welding wire that can improve the existence of post-weld pores and provide high-quality and stable post-weld structure while ensuring excellent post-weld bonding strength in view of the shortcomings of the prior art.

[0005] The technical solution adopted by the present invention to solve the first technical problem is: a tin bronze alloy welding wire, the mass percentage composition of the tin bronze alloy welding wire is: Sn: 7-13wt%, P: 0.02-0.15wt%, Zn: 0.005-0.1wt%, and other elements with a total amount of less than 3.5wt%, wherein the other elements are selected from one or more of Ni, Ti, Pb, Si and La, wherein Ni≤3.0wt%, Ti≤0.75wt%, Pb≤0.15wt%, Si≤0.1wt%, La≤0.1wt%, and the balance is Cu and unavoidable impurities.

[0006] Sn is the main alloying element in the tin bronze alloy welding wire of the present invention, which forms a limited solid solution with the Cu matrix, and can significantly improve the tensile strength, corrosion resistance and wear resistance of the alloy. If Sn is added to more than 7wt%, it can help improve the wettability of the welding wire on the surface of the solid base material and improve the welding forming effect; if the Sn content exceeds 13wt%, reverse segregation of Sn is likely to occur, resulting in the precipitation of hard and brittle compound precipitation phases with poor ductility in the alloy, reducing the processing performance of the alloy, and at the same time, in the subsequent processing process, holes are easily formed near the Sn-rich area with eutectoid structure, which is not conducive to the compactness of the alloy and the post-weld structure, and excessive Sn elements also increase the hot shortness tendency of the alloy. Therefore, the present invention controls the Sn content to 7-13wt%, and further, the Sn content is preferably 9-12wt%.

[0007] P is another main alloying element in the tin bronze alloy welding wire of the present invention. P acts as a deoxidizer and improves the casting properties of the alloy. If the P content is less than 0.02wt%, the fluidity and formability of the molten alloy liquid are reduced; if the P content exceeds 0.15wt%, it is easy to increase the reverse segregation at the grain boundary, and the low melting point compound formed by precipitation may become the starting point of crack formation, resulting in reduced alloy processing performance and affecting post-weld formability. Therefore, the present invention controls the P content to 0.02-0.15wt%.

[0008] The element Zn is added to the tin bronze alloy welding wire of the present invention, and Zn is solid-dissolved in the matrix phase of the tin bronze, which can improve the degree of alloying. If Zn is added to more than 0.005wt%, it can reduce the reverse segregation of elements such as Sn and P in the material, and at the same time play the role of improving the fluidity of the alloy and deoxidizer, which is beneficial to the refinement of the alloy structure and the improvement of the compactness of the alloy; if the Zn content exceeds 0.1wt%, the sliding performance of the alloy cannot be improved. At the same time, due to the low boiling point of Zn, the excessive Zn content in the alloy is easily volatilized under the influence of temperature during the subsequent welding process, thereby increasing the number of pores after welding and increasing the trend of pores after welding to change to large sizes. In general, a higher Zn content has a negative impact on the existence of pores after welding. Therefore, the present invention controls the Zn content to 0.005-0.1wt%.

[0009] The grain size and distribution in the microstructure of the tin bronze alloy welding wire of the present invention are affected by the content of the above-mentioned main alloying elements. Preferably, the content of Sn in the alloy is recorded as [Sn], the content of P in the alloy is recorded as [P], and the content of Zn in the alloy is recorded as [Zn], and F1 is set to be 0.7[Sn]-5[P]+0.5[Zn], and F1 satisfies: 5.2≤F1≤9.0. If F1 is greater than 9.0, a tin-rich phase is easily formed in the alloy, which is easy to produce microcracks, and the casting processing performance of the alloy is reduced. Therefore, in the present invention, the upper limit of F1 is set to 9.0, more preferably 8.9, and further preferably 8.7. On the other hand, if F1 is less than 5.2, the wettability of the welding wire is poor, which has an adverse effect on the forming performance of the copper-based cladding layer after the alloy welding and its post-weld bonding strength with the steel-based base material. Therefore, the present invention controls the lower limit of F1 to be 5.2, more preferably 5.5, and further preferably 5.7.

[0010] The tin-bronze alloy welding wire of the present invention may optionally contain one or more of Ni, Ti, Pb, Si and La in a total amount of less than 3.5wt%. Among them, Ni plays a role in inhibiting dendrite segregation, while refining the grains, increasing the strength, hardness and elastic limit value of the material, and the amount of Ni added should be controlled below 3.0wt%; Ti can form Ti-Sn compounds with Sn, which play a role in refining the grains and precipitation strengthening, and can increase the softening temperature and hardness of the tin-bronze alloy welding wire, while improving the welding stability of the material without sacrificing the thermal conductivity of the material, and the amount of Ti added should be controlled below 0.75wt%; Pb plays a role in improving the cutting performance and self-lubricating properties of the alloy, and improves the wettability of the welding wire, and the addition of Pb The amount of La added should be controlled below 0.15wt%; Si helps to improve the hardness and wear resistance of the alloy. If Ni is added at the same time, Ni-Si compounds can be formed to improve the strength of the alloy. The amount of Si added should be controlled below 0.1wt%; the addition of La significantly improves the corrosion resistance of the alloy, and improves the mechanical properties of the alloy such as hardness and plasticity. It can also reduce problems such as thermal cracking and deformation during alloy welding. At the same time, La can refine Pb particles, reduce friction coefficient, and improve the wear resistance and cutting performance of the alloy. The amount of La added should be controlled below 0.1wt%. If the above optional elements are added too much, the processing performance of the material will deteriorate. Therefore, the total amount of one or more elements of Ni, Ti, Pb, Si and La should be controlled below 3.5wt%.

[0011] The impurity elements in the tin-bronze alloy welding wire of the present invention include but are not limited to S, O, H, N, Al, Fe, Mn, etc. Preferably, the impurity element contents of Al, Fe, and Mn in the tin-bronze alloy welding wire of the present invention are strictly controlled to be less than 0.05wt%. The impurity elements such as Al, Fe, and Mn introduced into the tin-bronze alloy welding wire of the present invention during the production process will have an adverse effect when exceeding a certain content in the alloy. Excessive impurity elements are easy to segregate and precipitate between dendrites, weaken the intercrystalline bonding force, and reduce the strength of the alloy. At the same time, there is a greater tendency to oxidize during the heat treatment process or the heating process used for welding. The oxidized inclusions formed by oxidation are easy to exist on the surface of the alloy and the surface of the welding layer, affecting the toughness and weldability of the material, and have a negative impact on the processing performance of the alloy and the quality stability of the post-weld structure. Therefore, the present invention controls the contents of Al, Fe, and Mn in the impurities to be less than 0.05wt%, more preferably, to be less than 0.02wt%.

[0012] Preferably, the average grain size of the tin-bronze alloy welding wire of the present invention is 0.1-8 μm. The inventors have found that the tin-bronze alloy is advantageous in that, by controlling the average size of the fine grains to be no more than 8 μm, the weld can be better filled during welding and cladding of the welding material, reducing the gas and inclusions in the weld and fusion zone, and eliminating or improving the pore size and porosity after welding; and when the grain size is too small, due to the aggregation of the grain boundaries, the material strength is too high, which reduces the plasticity of the fusion zone after welding and increases the residual stress after welding. In severe cases, it may also lead to the occurrence of liquid metal embrittlement, causing the initiation and expansion of cracks in the matrix of the welded parent material, destroying the integrity of the parent material, so the present invention controls the fine grain size to be no less than 0.1 μm.

[0013] Preferably, the relative average deviation of the grain size on the cross section of the tin-bronze alloy welding wire of the present invention does not exceed 75%. The alloying degree of the tin-bronze alloy welding wire of the present invention is relatively high, and the α phase is the main matrix phase. The organization of the tin-bronze alloy of the present invention is effectively improved to obtain a uniform internal microstructure. The grain boundary bonding force between the uniform grain structures is relatively strong, which improves the stability of the overall performance of the alloy; in addition, the deformation coordination between the grains during welding is improved, which significantly improves the post-weld bonding strength and post-weld porosity. If the relative average deviation of the grain size is too large, the local cumulative strain increases, which has an adverse effect on the mechanical properties, wire output stability and the presence of post-weld porosity of the tin-bronze alloy welding wire.

[0014] If the content of hard particles containing Sn, Ni, P, etc. in tin bronze, i.e., other large-sized hard and brittle second phase particles that are not dissolved in the tin bronze alloy parent phase, is too high or unevenly distributed, it will cause cracks to appear along the hard phase segregation, within the grain or at the grain boundary during the processing of the tin bronze, affecting the processability. Preferably, in the tin bronze welding wire of the present invention, the number density of the coarse hard and brittle precipitate phase with a particle size of more than 0.1 μm is controlled to be no more than 3 / μm. 2 , in order to inhibit the local strain accumulation caused by the precipitation of coarse precipitates during crystallization, thereby avoiding the uneven size of recrystallized grains. At the same time, it can also inhibit the occurrence of local grain coarsening when the alloy is used under high temperature conditions.

[0015] The tensile strength of the tin-bronze alloy welding wire of the present invention is above 800MPa. During the welding process of the tin-bronze alloy welding wire of the present invention and the steel-based base material, the liquid tin-bronze contacts the steel-based base material. Due to the low density and coarse grains of the tin-bronze cladding layer, pores are generally present in the tin-bronze cladding layer. The large pores and excessive pores in the cladding layer reduce the effective working area of ​​the welding layer, and also cause the problem of stress concentration, which has an adverse effect on the bonding strength of the material, as well as the strength and plasticity of the welding layer. In order to ensure that the tin-bronze alloy welding wire of the present invention obtains a welding fusion zone with good density, few defects and further improved post-weld bonding strength after welding, preferably, the post-weld bonding strength of the copper-based cladding layer formed after the tin-bronze alloy welding wire of the present invention is welded to the steel base and is not less than 250Mpa. A 4mm×5.5mm field of view is taken as an observation area on any longitudinal section of the copper-based cladding layer. In the observation area, the size of each post-weld pore does not exceed 250μm, and the area of ​​all post-weld pores does not exceed 2%.

[0016] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned tin-bronze alloy welding wire.

[0017] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing a tin bronze alloy welding wire, comprising the following steps: smelting → casting → homogenization annealing → cold working + planing → stress relief annealing → diameter reducing drawing.

[0018] Melting and casting: The melting and casting temperature is 1050-1250℃, and the casting is continuous casting. In the final insulation stage of smelting, electromagnetic stirring is carried out for 5-10 minutes, and the stirring current frequency is 5-20Hz, which accelerates the diffusion of elements such as Cu, Sn, and P in the molten alloy and effectively ensures the uniformity of the alloy composition. Continuous casting is carried out at a casting speed of 0.1-1m / min, the casting time is 0.05-5s, and the pulling stop time is 0.05-3s, so that the molten alloy obtains a suitable initial solidification temperature. As the temperature decreases, the liquid phase in the tin-bronze alloy liquid gradually transforms into the solid phase. If the cooling rate of continuous casting is too high and the alloy is too undercooled, it may cause the surface of the continuous casting billet to be rough or even cracked, affecting the subsequent processing; if the cooling rate of continuous casting is too low, coarse columnar crystals are easily formed in the alloy structure, the number of reverse segregation channels increases, and the δ, Cu 3 P、SnO 2 Therefore, the average cooling rate of the continuous casting is controlled to be 10-10 3 ℃ / s, in order to effectively inhibit the dendrite growth and reverse segregation of primary α in tin bronze alloy, reduce shrinkage, shrinkage holes and other problems, and at the same time help to reduce the tendency of grain growth in subsequent processing to obtain a grain-refined alloy.

[0019] Homogenizing annealing: There is dendrite segregation of Sn and uneven dispersion of δ phase in the continuous casting billet obtained by continuous casting. In order to improve this unevenness and obtain a tin bronze alloy homogenized continuous casting billet with further uniform distribution of elements and organization, the continuous casting billet is subjected to homogenizing annealing. Before homogenizing annealing, in the charging stage of the continuous casting billet, refractory wool is placed under the billet to prevent the billet from deforming; in the insulation stage, the base fan of the heating furnace is turned on at the same time to make the gas in the heating furnace convect and ensure the temperature uniformity of the furnace and the billet; the annealing temperature is 620-670℃, and the insulation time is 120-180min. In order to further limit the precipitation of large-sized precipitates in the alloy and fully improve the unevenness of the organization of the continuous casting billet, preferably, the cooling process after homogenizing annealing is controlled, that is, the average cooling rate in the temperature range of 630-300℃ is controlled to be 0.1-20℃ / min, and the average cooling rate in the temperature range of 300-100℃ is controlled to be 1-50℃ / min. In addition, in order to suppress oxidation on the surface of the blank as much as possible, the homogenization annealing atmosphere is an inert gas, preferably nitrogen, and the gas flow rate blown in is 60-250 L / min.

[0020] Cold processing + planing: The processing rate of cold processing is controlled at 50-60%. During the cold processing, a planing mold is used to remove surface defects and oxide layers of the blank to ensure the appearance of the finished product. The planing amount is about 0.1-0.15mm.

[0021] Stress relief annealing: Stress relief annealing is carried out at a temperature range of 620-670℃ for 120-180min to remove residual stress in the alloy to ensure the machinability of the alloy in the subsequent diameter reduction and drawing process.

[0022] Reducing drawing: The billet after stress relief annealing is subjected to multiple reducing drawing until the final wire diameter used as welding wire product is reached. In the reducing drawing process, the stretching coefficient of each pass is 0.30-0.75, where the stretching coefficient is the ratio of the cross-sectional area of ​​the billet after stretching to the cross-sectional area of ​​the billet before stretching. If the stretching coefficient is greater than 0.75, the degree of grain deformation is too small, resulting in the refinement of the edge grains in the alloy, and the larger grains at the edge and the center, which is easy to increase the relative average deviation of the grain size in the alloy structure; if the stretching coefficient is less than 0.30, as the deformation increases, dislocations are likely to accumulate near the grain boundaries, the material strength and hardness rise rapidly, and the plasticity drops sharply, which is easy to cause wire breakage problems in subsequent production. Preferably, as required, an intermediate annealing heat treatment is included between at least two passes of the diameter reducing drawing process, the holding temperature of the intermediate annealing heat treatment is 400-700°C, and the holding time of the intermediate annealing heat treatment and the wire diameter of the aisle billet before the intermediate annealing heat treatment satisfy the following relationship: T=K×D, wherein T is the holding time of the intermediate annealing heat treatment, in h; K is any value in the range of 0.2-3; D is the wire diameter of the aisle billet before the intermediate annealing heat treatment, in mm. Preferably, in the diameter reducing drawing process, the finished product drawing speed is 120-300m / min, and the appropriate finished product drawing speed can further ensure that the final welding wire product obtains the desired organizational characteristics, and ensures the wire feeding stability in the subsequent welding process and the improvement effect of the post-weld organization.

[0023] Compared with the prior art, the present invention has the following advantages: in the tin-bronze alloy welding wire of the present invention, appropriate amounts of P and Zn are added simultaneously, the addition amounts of Sn, P and Zn are limited, and the contents of Al, Fe and Mn in the impurities are strictly controlled to be no more than 0.05wt%, respectively, so that a tin-bronze alloy having an average grain size of the matrix phase adjusted within the range of 0.1-8μm can be obtained. Moreover, while having such an appropriate average grain size of the matrix phase, the relative average deviation of the grain size on the cross section of the tin-bronze alloy welding wire is adjusted to no more than 75%, and the number density of the coarse hard and brittle precipitate phase with a grain size of more than 0.1μm is further limited to no more than 3 / μm. 2, so that the tin-bronze alloy can be easily processed to obtain the alloy welding wire of the required wire diameter, and at the same time, the growth of grains during welding can be effectively suppressed, a uniform post-weld structure can be obtained, and the existence of pores in the copper-based cladding layer after welding can be significantly improved, so as to obtain a post-weld working layer with excellent molding effect and performance. The tensile strength of the tin-bronze alloy welding wire of the present invention is above 800MPa, and the post-weld bonding strength between the copper-based cladding layer formed after welding with the steel substrate and the steel-based parent material is not less than 250Mpa. A 4mm×5.5mm field of view is taken as the observation area on any longitudinal section of the copper-based cladding layer. In the observation area, the size of each post-weld pore does not exceed 250μm, and the area of ​​all post-weld pores does not exceed 2%. The tin-bronze alloy welding wire of the present invention can be used for welding and repair in wind power, nuclear power, shipbuilding, automobile, petroleum and other industries, as well as welding as a working layer of elastic elements and wear-resistant parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is an optical microscope photo of the welding wire sample of Example 11 after welding (25 times);

[0025] Figure 2 This is an optical microscope photograph (25 times) of the welding wire sample of Comparative Example 3 after welding. DETAILED DESCRIPTION

[0026] In order to further explain the technical solution of the present invention, 13 embodiments and 4 comparative examples are selected below to elaborate the present invention in detail, but the present invention is not limited to these embodiments. The alloy components of each embodiment and comparative example are shown in Table 1, and the microstructure and properties of the alloy are shown in Table 2.

[0027] According to the alloy components of Examples 1-13 and Comparative Examples 1-4 in Table 1, the corresponding raw materials were weighed. The melting temperature was 1100-1250°C, and electromagnetic stirring was performed for 5-10 minutes in the final insulation stage of smelting, and the stirring current frequency was 5-20Hz. After smelting, continuous casting was performed, with a casting speed of 0.5m / min, pulling for 4s and stopping for 2s, and an average cooling rate of 10-10 3The above billet was homogenized and annealed at 630°C for 180 min, first cooled to 300°C at an average cooling rate of 0.1-20°C / min, and then cooled from 300°C to 100°C at an average cooling rate of 1-50°C / min. The annealing atmosphere was nitrogen, and the gas flow rate was 200L / min. The homogenized annealed billet is cold drawn to Φ9mm, and then shaved by 0.1mm; then the cold drawn billet is subjected to stress relief annealing at 620-670℃ for 120-180min; finally, a diameter reducing drawing process is performed, specifically: the billet is drawn from Φ9mm to Φ1.3mm through 7 drawing passes, and then the Φ1.3mm billet is drawn to a Φ1.0mm tin bronze welding wire product at a drawing speed of 120-300m / min, wherein the temperature of the intermediate annealing heat treatment between each pass is 400-700℃, and the holding time of the intermediate annealing heat treatment and the wire diameter of the aisle billet before the intermediate annealing heat treatment satisfy the following relationship: T=K×D, wherein T is the holding time of the intermediate annealing heat treatment, in h; K is any value in the range of 0.2-3; D is the wire diameter of the aisle billet before the intermediate annealing heat treatment, in mm.

[0028] The tin bronze alloy welding wire of the above embodiment has a more uniform microstructure than the comparative alloy within the alloy composition range and composition relationship range defined in the present invention, and its average grain size is controlled within the range of 0.1-8 μm, and the relative average deviation of the grain size is controlled within 75%. At the same time, the number density of the precipitated phase with a particle size of more than 0.1 μm is ≤3 / μm. 2 , with better post-weld bonding strength and significantly improved post-weld porosity, showing better post-weld structure and structure of the copper-based cladding layer.

[0029] Samples were cut out from the final tin-bronze alloy welding wire product obtained above, and the organization and performance were analyzed according to the following standards and methods. The results are shown in Table 2.

[0030] Microstructure observation: The cross section of the sample was selected for grinding and polishing, and the sample was etched with ferric chloride hydrochloric acid alcohol solution. The grain size was observed at 5000× using a TESCAN S9000 scanning electron microscope. Three fields of view were randomly collected for each sample, and the typical grain size was measured using electron microscope analysis software and the average grain size value was calculated. The smallest or largest grain in the field of view was selected, and the difference between it and the average grain size was measured and analyzed. The relative average deviation of the grain size was calculated by the ratio of the difference to the average grain size value. The precipitated phase was observed under a scanning electron microscope, and the number of precipitated phases with a particle size of more than 0.1μm was calculated and counted based on the observation results, and their number density was calculated and counted.

[0031] Tensile strength: Tested on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2021 Tensile tests on metallic materials - Part 1: Room temperature test methods.

[0032] The post-weld performance test uses Q235 steel as the steel matrix. The specimens are prepared according to Article 5.4.2 of GB / T 8110-2008 Carbon Steel and Low Alloy Steel Welding Wire for Gas Shielded Arc Welding. With reference to the welding specifications in the standard, this alloy is welded with a diameter of Φ1.0mm. Before welding, the specimens are preheated at 100°C for 30-45min and the surface is polished. The welding equipment is a Yaskawa MOTOMAN-AR1730 welding robot, using pulse MIG welding, welding current 223A, welding voltage 13.4V, welding speed 10m / min. Pay attention to the welding surface during welding, and polish it every time the welding robot stops.

[0033] Post-weld bonding strength: The specimens were processed and tested in accordance with GB / T12948-1991 Destructive Test Method for Bimetallic Bond Strength of Sliding Bearings. Through wire cutting and lathe processing, the welded specimens were made into a weld layer with a thickness of 3mm and a post-weld bonding area of ​​200mm. 2 The test sample is then stacked up from top to bottom. During the test, the downward pressure of the universal testing machine on the pressure block is transmitted to and acts on the copper layer of the sample. The maximum pressure recorded when the copper layer is destroyed is the post-weld bonding strength between the copper-based cladding layer and the steel-based base material.

[0034] Post-weld pore size and pore area ratio: The specimens were mechanically polished, and three 4mm×5.5mm fields of view were randomly selected as observation areas on the longitudinal section of the copper-based cladding layer of each specimen. The pore size in the metallographic photo was measured under a 25x metallographic microscope, and the maximum pore size observed was recorded as the maximum post-weld pore size; the area occupied by the pores was analyzed by the software provided by the metallographic microscope, and the area ratio of all post-weld pores in each observation area was calculated. Among them, the post-weld optical microscope photo of the welding wire sample of Example 11 is shown in Figure 1 The optical microscope photo of the welding wire sample of comparative example 3 after welding is shown in Figure 2 . Figure 1 The arrows in the middle indicate numbers ①, ②, and ③, which represent three post-weld pores. The sizes of the three post-weld pores are 228.46μm, 98.57μm, and 56.82μm, respectively. Figure 2 The numbers ④, ⑤, and ⑥ indicated by the middle arrows represent three post-weld pores, and the sizes of the three post-weld pores are 418.86 μm, 174.48 μm, and 63.81 μm, respectively.

[0035] Table 1 Alloy composition and composition relationship of the embodiments of the present invention and the comparative examples

[0036]

[0037] Table 2 Microstructure and properties of alloys in the embodiments of the present invention and comparative examples

[0038]

Claims

1. A tin bronze alloy welding wire, characterized in that: The tin bronze alloy welding wire has a mass percentage composition of: Sn: 7-13wt%, P: 0.02-0.15wt%, Zn: 0.005-0.1wt%, and other elements with a total amount of less than 3.5wt%, wherein the other elements are selected from one or more of Ni, Ti, Pb, Si and La, wherein Ni≤3.0wt%, Ti≤0.75wt%, Pb≤0.15wt%, Si≤0.1wt%, La≤0.1wt%, and the balance is Cu and unavoidable impurities.

2. The tin-bronze alloy welding wire according to claim 1, characterized in that: The contents of Al, Fe and Mn contained in the impurities in the mass percentage composition of the tin bronze alloy welding wire are: Al≤0.05wt%, Fe≤0.05wt%, and Mn≤0.05wt%.

3. The tin-bronze alloy welding wire according to claim 1, characterized in that: The Sn content is recorded as [Sn], the P content is recorded as [P], and the Zn content is recorded as [Zn]. Let F1 = 0.7[Sn] - 5[P] + 0.5[Zn], and F1 satisfies: 5.2≤F1≤9.

0.

4. The tin-bronze alloy welding wire according to claim 1, characterized in that: The average grain size of the tin-bronze alloy welding wire is 0.1-8 μm, and the relative average deviation of the grain size on the cross section of the tin-bronze alloy welding wire does not exceed 75%.

5. The tin-bronze alloy welding wire according to claim 1, characterized in that: The number density of the precipitated phase with a particle size of 0.1 μm or more in the tin-bronze alloy welding wire is not greater than 3 / μm 2 .

6. The tin-bronze alloy welding wire according to claim 1, characterized in that: The tensile strength of the tin-bronze alloy welding wire is above 800MPa, and the post-weld bonding strength between the copper-based cladding layer formed after the tin-bronze alloy welding wire is welded to the steel substrate and the steel-based parent material is not less than 250Mpa. A 4mm×5.5mm field of view is taken as an observation area on any longitudinal section of the copper-based cladding layer. In the observation area, the size of each post-weld pore does not exceed 250μm, and the area of ​​all post-weld pores does not exceed 2%.

7. A method for preparing the tin bronze alloy welding wire according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: smelting→casting→homogenizing annealing→cold working+planing→stress relief annealing→reducing and drawing, wherein, in the cooling process after the homogenizing annealing, the average cooling rate in the temperature range of 630-300°C is 0.1-20°C / min, and the average cooling rate in the temperature range of 300-100°C is 1-50°C / min.

8. The method for preparing the tin bronze alloy welding wire according to claim 7, characterized in that: In the smelting process, electromagnetic stirring is performed for 5-10 minutes in the final insulation stage of smelting, and the stirring current frequency is 5-20Hz; the casting is continuous casting, and the continuous casting casting speed is 0.1-1m / min, the casting time is 0.05-5s, the pulling stop time is 0.05-3s, and the average cooling rate is 10-10 3 ℃ / s.

9. The method for preparing the tin bronze alloy welding wire according to claim 7, characterized in that: In the reducing drawing process, the stretching coefficient of each pass is 0.30-0.75, and the drawing speed of the finished product is 120-300m / min.

10. The method for preparing the tin bronze alloy welding wire according to claim 7, characterized in that: An intermediate annealing heat treatment is included between at least two passes of the reducing drawing process. The holding temperature of the intermediate annealing heat treatment is 400-700°C. The holding time of the intermediate annealing heat treatment and the wire diameter of the aisle billet before the intermediate annealing heat treatment satisfy the following relationship: T=K×D, wherein T is the holding time of the intermediate annealing heat treatment, in h; K is any value in the range of 0.2-3; D is the wire diameter of the aisle billet before the intermediate annealing heat treatment, in mm.